Effect of carissa edulis (VAHL) apocynaceae stem bark on hematological parameters in ccl¬4 induced albino rats - Y. Izam, Y.; B. Bukar, B. (International Journal of Pharmacology and Toxicology, 2021)
Aim/Objectives: There are claims that Carissa edulis has positive effects on hematological parameters. The present study was conducted to evaluate the safety and claimed hematological effect of Carissa edulis on rats intoxicated with carbon tetrachloride.Method: Thirty six male albino rats were randomly allotted to six groups of six rats per group. The animals were treated with (250, 500 and 1000mg/kg of the stem bark extract of Carissa edulis. The extract was administered daily by gavage to the animals for 28 consecutive days. The 50%v/v Carbon tetrachloride (CCl4) and olive oil was gavaged twice a week. The animals of the normal control group were given 5ml/kg of distilled water while those of the CCl4 group were administered CCl4 only twice a week.Result: Results of the study showed that the CCl4 group caused a significant decrease in most of the hematological parameters while the extract treated groups showed a significant increase in these parameters.Discussion / Conclusion: This suggests that the ethanolic stem bark extract has erythropoietic, thrombopoietic and positive effect on the immune system.
Keywords: Carissa edulis; Thrombopoietin; Erythropoietin; Hematological Parameters; CCl4 and Gavage.